WORKING WITH PRESCHOOL CHILDREN WITH DEFECTS AND PREPARING THEM FOR SCHOOL (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Compulsory schooling places certain demands on a child. It is known that a child must reach a level of development that can meet the requirements of the educational institution, and only then can the child be sent to school. In this process, it is important to prepare the child for school education, which is why the article explores the importance of preparing preschool children for school education.